Prevalence and treatment of HIV/AIDS in Pakistani population: A retrospective study - Hafiza Tania Naveel; Sabiha Gul; Farzana Sadaf; Ahmed Bokhari, Syed Waleed; Sidra Afzal; Abdul Wasay Mahmood (Journal of the Pakistan Medical Association, 2023)
HIV/AIDS epidemic poses an emerging threat around the world. An estimated 0.1% of people aged 15 to 49 years have been infected with HIV/AIDS in Pakistan during the last few years. This research study aims to analyse the prevalence and treatment/management of HIV/AIDS among the Pakistani population aged 15 to 45 years from 1990 to 2020 and this research data was collected during the year 2021. The analysis was done by using E-views software. Descriptive statistical analysis, correlation coefficient, unit root analysis, and linear regression analysis were used. Results indicated that there is low awareness regarding AIDS in the population and there is a significant link between prevalence and population increase, i.e. with the increase in population the prevalence of AIDS also increases. Findings are discussed in terms of implications for prevention and education of HIV/AIDS in Pakistan’s population. Keywords: Prevalence (P), Therapy (T), Human Immunodeficiency Virus (HIV).